The quantum universe (and why anything that can happen, does) - Cox, Brian 1968- (Da Capo Press, 2012)
The Quantum Universe brings together two authors on a brilliantly ambitious mission to show that everyone can understand the deepest questions of science. But just what is quantum physics? How does it help us understand the universe? Where does it leave Newton and Einstein? And how - for all its apparently counter-intuitive ideas - can we be sure that the theory is good? The bizarre behaviour of the atoms and energy that make up the universe has lead to some woolly pronouncements on the nature of all interconnectedness - but Brian Cox and Jeff Forshaw reveal the simple and understandable theories that allow for concrete, yet astonishing, predictions about the world around us. From entangled twins to the incredible double-slit experiment, The Quantum Universe will give every reader the most up-to-date picture of that amazing subatomic world, where thousands of years of physics must be rewritten completely